Cochlear implantation in children with congenital long QT syndrome: Introduction of an evidence-based pathway of care. (2nd November 2018) - Scott-Warren, Victoria; Bendon, Anju; Bruce, Iain A.; Henderson, Lise; Diacono, Jacques
Abstract : Congenital long QT syndrome (cLQTS) is an inherited cardiac ion channelopathy characterized by a long corrected-QT interval on the ECG, associated with a risk of syncope and sudden death as a result of arrhythmias. The archetypal arrhythmia associated with cLQTS is torsade de pointes which may degenerate into ventricular fibrillation. Children with Jervell and Lange-Neilsen syndrome have the combination of cLQTS and congenital sensorineural deafness and may present for cochlear implantation (CI). Sympathetic stimulation and administration of QT-prolonging medications may trigger arrhythmias in children with cLQTS and thus the perioperative period is a time of increased risk of adverse events, with deaths reported in the CI literature. Our Paediatric Cochlear Implant Programme had previously elected to discontinue offering CI to children with cLQTS following a perioperative death. However, subsequent demand for this service by parents led us to develop and introduce a multidisciplinary, evidence-based pathway of care. This pathway modifies the perioperative management of these children to reduce the associated risk. We present the cases of four children with cLQTS who underwent CI in our specialist children's hospital.